Communication Education and Accreditation in Open and Distance Learning in the Digital Age: The Experience of National Open University of Nigeria (NOUN) - Onwubere, Chidinma Henrietta; Ekeanyanwu, Nnamdi Tobechukwu; Aliede, Jonathan Elom (West African Journal of Open and Flexible Learning, 2017)
This paper discusses communication education and accreditation in Open and Distance Learning in the Digital Age. The paper takes a critical look at the history of Distance Education (DE) and the need for Open and Distance Education (ODE) in Nigeria. It reviews the circumstances leading to the establishment of the National Open University of Nigeria (NOUN) and her role in the promotion of DE in the country. It outlines NOUN academic programmes and discusses the Bachelor of Science programme in Mass Communication. We argue in this paper that the use of the same Benchmark Minimum Academic Standard (BMAS) used to accredit regular programmes of communication in regular universities should not be used to accredit the communication programme of NOUN because of the various differences in the mode of operation and delivery of expectations. NUC should, therefore, gather ODE experts in the related disciplines to design a unique template that accommodates the uniqueness of the ODE. Otherwise, the government should institute a different body to handle accreditation of ODE platforms or the NUC itself should set up a Special Unit within its Commission to oversee the operations of NOUN and other related institutions. Résumé : Cet article traite la formation en communication médiatique et sa réglementation dans le système de l’enseignement à distance à l’ère du numérique. L’article jette un regard critique sur l’histoire de l’enseignement à distance (DE) et sur la nécessité d’un enseignement ouvert et à distance (ODE) au Nigeria. Il passe en revue les circonstances qui ont conduit à la création de l’Université nationale de l’enseignement à distance du Nigeria (NOUN) et son rôle dans la promotion de l’ED dans le pays. Il donne un aperçu des programmes académiques du NOUN et il discute aussi le baccalauréat en communication médiatique. Nous soutenons dans cet article que l’utilisation de la même Norme académique minimale de référence (BMAS) utilisée pour la régler la formation en communication médiatique dans les universités régulières ne devrait pas être utilisée pour régler la formation en communication médiatique du NOUN en raison des diverses différences dans la façon de formation de fonctionnement et la réalisation des attentes. La commission pour les universités au Nigeria devrait, donc, mettre en place un conseil des spécialistes de l’enseignement à distance pour concevoir un modèle unique qui tienne compte du caractère unique de l’enseignement à distance. Si non, le gouvernement devrait mettre en place un organisme différent pour s’occuper de la réglementation de l’enseignement à distance. Ou bien, la commission pour les universités elle-même devrait créer une unité spéciale au sein de la commission pour superviser les opérations de la COU et d’autres institutions connexes.